2019
DOI: 10.1038/s41591-018-0324-z
|View full text |Cite
|
Sign up to set email alerts
|

Healthy infants harbor intestinal bacteria that protect against food allergy

Abstract: There has been a striking generational increase in life-threatening food allergies in Westernized societies 1 , 2 One hypothesis to explain this rising prevalence is that 21 st century lifestyle practices, including misuse of antibiotics, dietary changes, and higher rates of Caesarean birth and formula feeding have altered intestinal bacterial communities; early life alterations may be particularly detrimental. 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
348
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 361 publications
(359 citation statements)
references
References 54 publications
9
348
0
2
Order By: Relevance
“…[97][98][99] Several recent studies have demonstrated that colonization of mice with fecal microbiota from food-allergic children does not protect the animals from food allergy, whereas colonization with microbiota from healthy children was protective. 100,101 While these studies and others suggest that multiple mechanisms might be involved, including but not limited to altered IgA reactivity, induction of regulatory cell subsets, or modification of epithelial metabolism, the consistent important finding is that the intestinal microbiome regulates allergic responses to dietary antigens and targeting the microbiome might be therapeutically effective in food allergy.…”
Section: Antigenmentioning
confidence: 99%
“…[97][98][99] Several recent studies have demonstrated that colonization of mice with fecal microbiota from food-allergic children does not protect the animals from food allergy, whereas colonization with microbiota from healthy children was protective. 100,101 While these studies and others suggest that multiple mechanisms might be involved, including but not limited to altered IgA reactivity, induction of regulatory cell subsets, or modification of epithelial metabolism, the consistent important finding is that the intestinal microbiome regulates allergic responses to dietary antigens and targeting the microbiome might be therapeutically effective in food allergy.…”
Section: Antigenmentioning
confidence: 99%
“…Finally, antibiotic treatment of neonatal mice enhances the susceptibility towards food allergen sensitization and experimental psoriasis . Also in humans, exposure to microbial constituents protects children from asthma development and specific bacterial species have been identified and shown to protect from food allergy . Conversely, early‐life antibiotic treatment alters the metabolome through alteration of the microbiota and increases the risk of obesity and allergies .…”
Section: The Maturation Of the Adaptive Mucosal Immune Systemmentioning
confidence: 99%
“…No significant differences in fecal scores were recorded between HC-S and HC-NS, which may indicate a protective effect of healthy microbiota upon allergen exposure as we and others observed previously. 3,4 In addition, clinical scores (scratching/ puffiness/ loss of mobility) after oral challenge with β-lactoglobulin (BLG) were significantly higher in CMA-S group versus CMA-NS and HC-S groups ( Figure 2B). Minimal differences in mouse mast cell protease 1 (mMCP-1) and allergen-specific sensitization markers were observed between the two fecal transfers ( Figure 2C-E), which contrasted with the increases observed in total IgE levels and total IgG1/IgG2a ratio in CMA-S and CMA-NS groups compared with HC-S and HC-NS groups, respectively ( Figure 2F,G).…”
Section: Gut Microbiota From Infant With Cow's Milk Allergy Promotes mentioning
confidence: 99%